Higher fraction of inspired oxygen during anesthesia increase the risk of postoperative pulmonary complications in patients undergoing non-cardiothoracic surgery: a retrospective cohort study - Wang, Tianzhu; Zhao, Weixing; Ma, Libin; Wu, Jing; Ma, Xiaojing; Liu, Luyu; Cao, Jiangbei; Lou, Jingsheng; Mi, Weidong; Zhang, Changsheng (Frontiers in Physiology, 2024)
Objective: The ideal intra-operative inspired oxygen concentration remains controversial. We aimed to investigate the association between the intraoperative fraction of inspired oxygen (FiO2) and the incidence of postoperative pulmonary complications (PPCs) in patients undergoing non-cardiothoracic surgery.This was a retrospective cohort study of elderly patients who underwent noncardiothoracic surgery between April 2020 and January 2022. According to intraoperative FiO2, patients were divided into low (≤ 60%) and high (>60%) FiO2 groups. The primary outcome was the incidence of a composite of pulmonary complications (PPCs) within the first seven postoperative days. Propensity score matching (PSM) and inverse probability treatment weighting (IPTW) were conducted to adjust for baseline characteristic differences between the two groups. Multivariate logistic regression analysis was used to calculate the odds ratios (OR) for FiO2 and PPCs.Results: Among the 3515 included patients with a median age of 70 years (interquartile range: 68-74), 492 (14%) experienced PPCs within the first 7 postoperative days. Elevated FiO2 was associated with an increased risk of PPCs in all the logistic regression models. The OR of the FiO2>60% group was 1.252 (95%CI 1.015-1.551, P = 0.038) in the univariate analysis. In the multivariate logistic regression models, the ORs of the FiO2>60% group were 1.259 (Model 2), 1.314 (Model 3), and 1.32 (model 4). A balanced covariate distribution between the two groups was created using PSM or IPTW. The correlation between elevated FiO2 and an increased risk of PPCs remained statistically significant with PSM analysis (OR, 1.393; 95% CI, 1.077-1.804; P = 0.012) and IPTW analysis (OR, 1.266; 95% CI, 1.086-1.476; P = 0.003).Conclusions: High intraoperative FiO2 (>60%) was associated with the postoperative occurrence of pulmonary complications, independent of predefined risk factors, in elderly non-cardiothoracic surgery patients. High intraoperative FiO2 should be applied cautiously in surgical patients vulnerable to PPCs.